CONVERSATIONAL IMPLICATURE IN THE SUBJECT GROUP BETWEEN LECTURERS AND ENGLISH EDUCATION DEPARTMENT STUDENTS BATCH 2020 AT MUSAMUS UNIVERSITY - Aldianus Tuwar; Rawuh Yuda Yuwana (Acceleration: Multidisciplinary Research Journal, 2023)
An idea or attitude that is conveyed through verbal or non-verbal forms, is not necessarily an attitude, and the intention can be appropriate but can be different or even the opposite of what is stated. The process of conveying meaning indirectly is known as conversational implicature. Therefore, this study aims to describe the form/function of conversational implicatures and the meaning in utterances. The method used is the see method. The results obtained related to the form/function of the implicature are the use of representative (assertive), directive (implosives), expressive, commissive, and declarative utterances. Furthermore, the violation of the principle of cooperation and all its maxims further accentuates clashes and games (joking).